Notice that the 2 expressions have 2 common terms.
(r-s) is just (s-r) times (-1)
similarly
(t-s) is just (s-t) times (-1)
this means that :
(r-s) (t-s) + (s-r) (s-t)=-(s-r)[-(s-t)]+(s-r) (s-t)
the 2 minuses in the first multiplication cancel each other so we have:
-(s-r)[-(s-t)]+(s-r) (s-t)=(s-r) (s-t)+(s-r) (s-t)=2(s-r) (s-t)
Answer:
d)<span>2(s-r) (t-s) </span>
First convert the rate into a decimal.
8/100=0.08
Next put all those numbers 15,000, 0.08, and 6 into the equation A=P(1+(rt)).
This is how you do it.
A=15,000(1+(0.08*6))
A=15,000(1+0.48)
A=15,000(1.48)
A=22,200
Answer:
No
Step-by-step explanation:
Answer:
True ( A )
Step-by-step explanation:
4 ( 5 ) - 2 = 2 ( 5 ) + 8
20 - 2 = 10 + 8
18 = 18
This is a correct statement because 18 does equal 18
If you would like to write x^4y - 4x^2y - 5y in a completely factored form, you can do this using the following steps:
x^4y - 4x^2y - 5y = y * (x^4 - 4x^2 - 5) = y * (x^2 + 1) * (x^2 - 5)
The correct result would be <span>y * (x^2 + 1) * (x^2 - 5).</span>